Characteristics of pulmonary Mycobacterium avium complex disease diagnosed later in follow-up after negative mycobacterial study including bronchoscopy. Issue 10 (October 2015) - Koyama, Kazuya; Ohshima, Nobuharu; Kawashima, Masahiro; Okuda, Kenichi; Sato, Ryota; Nagai, Hideaki; Matsui, Hirotoshi; Ohta, Ken
Abstract: Background: We occasionally experience cases suspected of pulmonary Mycobacterium avium complex (MAC) disease without positive bacterial cultures. Objective: To evaluate features of pulmonary MAC cases diagnosed later in the follow-up after negative intensive investigation. Methods: We defined and compared three groups; the first study negative (FSN) group, the first study positive (FSP) group, and MAC negative group. The FSN group consisted of patients negative for MAC isolation by bronchial washing performed between 2007 and 2011, but positive later. Patients with positive MAC cultures in the first study were incorporated into the FSP group. MAC negative group consisted of MAC suspects without MAC isolation in the follow-up. Results: Twenty-four patients were classified as FSN group, 61 as MAC negative group and 265 as FSP group. FSN group exhibited more solitary nodule pattern (n = 7 in FSN, n = 6 in FSP; p < 0.001) and less nodular/bronchiectatic (NB) diseases (n = 17 in FSN, n = 245 in FSP; p < 0.001). When limited to NB type, the FSP group had more cavitations (6% in FSN, 32% in FSP; p = 0.028). Patients with more than three lung lobes involved were more frequent in the FSN group compared with FSP group with negative sputum cultures (65% vs 34%; p = 0.014) and with MAC negative group (65% vs 28%; p = 0.009). Conclusions: Patients diagnosed as pulmonary MAC disease in the follow-up duration tend to show solitary nodular pattern or NB pattern without cavitation. In FSN patients with NB pattern, more lung lobes were involved in the first study, suggesting subsequent MAC infection onto the underlying ectatic bronchi. Highlights: We reviewed the FSN group defined as cases with positive conversion of MAC cultures. The FSN group showed nodular or nodular/bronchiectatic (NB) pattern frequently. In NB cases, the FSN group showed more involved lung lobes than mild MAC cases. Wider area of bronchiectasis was related to higher risk for subsequent MAC infection.